Взаємодія електромагнітного випромінювання з металевими наношарами на поверхні твердого тіла - Lerman, L. B.; Lucshenko, M. O.; Suchoruchko, Ya. S. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The problem of interaction of electromagnetic radiation with the arbitrary number of different flat metallic nanoslabs divided two dielectric half-spaces is solved. Expressions of complex reflection coefficient and transmission coefficient, their modules and phases, and also values of these coefficients on power are found with using impedance method. The developed method allows to investigated the both frequency dependences of coefficients at fixed angles of falling waves and angular dependence for a select frequency range. Graphic material which illustrates possibilities of the developed approach is resulted. In particular, dependences of coefficients are pointed on durability from length of plain wave in the cases of perpendicular and parallel polarizations for one-layer covering from gold or silver, and also for two-layer covèring from silver and gold.